Family Ties Between The British and German Throne (1888-1910) - حسـن مغتاظ التميمي, ماريا (Al-Adab Journal, 2018)
The family ties between Britain and Germany formed a central axis in the conduct of policy between the two countries during the period (1888-1910), as Queen Victoria tried to make the attitudes of Britain and Germany unified both in Europe and abroad, but those aspirations ran into personal rivalry between Crown Prince Edward And the Kaiser of Germany Wilhelm II because both kings have strong personal and stubborn.Edward Wilhelm was the son of his sister and not the emperor of Germany, although Wilhelm became the King of Germany before his uncle Edward came to the throne of Britain.Thus, Edward regarded the German Empire as being more modern than the British Empire. The British monarchy of Prince Edward as a rebellious person against his mother Queen Victoria for alcohol, smoking, gambling and a lot of other bad deeds, while Wilhelm was the son of the beloved daughter of her mother Queen Victoria, who was characterized by recklessness, He was an Englishman and a German who had no clear evidence to guide them in these two worlds, and failed to show respect for Edward.The rivalry between the British and German monarchs grew so intense that they brought their countries into the circle of personal rivalry and rivalry between them.